Implementation of Project Management in the Development of an Android-Based Household Waste Monitoring System using JIRA Software - Bunga, Munengsih Sari; Gernowo, Rahmat; Ishlakhuddin, Fauzan; Mulyani, Esti; Fikri, Moh Ali; Rosyalia, Syofi (Jurnal Sistem Informasi Bisnis, 2025)
The increasing amount of household waste presents a major environmental challenge, worsened by inefficient and outdated waste management practices. Traditional systems lack real-time monitoring and responsiveness, creating a gap in timely waste management. This research introduces a creative solution through the development of an Android-based Household Waste Monitoring System, integrating Internet of Things (IoT) technology to provide real-time data on waste bin capacities and immediate notifications. Unlike conventional approaches, this system creatively bridges the gap by enabling proactive waste management through instant alerts and real-time tracking, allowing users to act before issues escalate. The system development follows an Agile/Scrum framework, fostering rapid iteration and user-driven enhancements. Through the innovative application of IoT and Agile methodologies with JIRA Software, this solution effectively addresses the inefficiencies of current waste management systems, as evidenced by an 80% success rate across five testing activities. This creative approach not only improves development efficiency but also accelerates adaptability in response to evolving waste management needs.